UJI AKTIVITAS ANTIOKSIDAN DALAM BEBERAPA MINUMAN YOGHURT DENGAN METODE DPPH (1,1-Diphenyl-2-Picryhydrazil) - Simarmata, Yettrie; Sinaga, Eka Margaret; Silitonga, Maringan (Jurnal Farmanesia, 2018)
Antioxidants are chemical compounds that can donate one or more electrons (electron donors) to free radicals to inhibit oxidative reactions. One example that has the potential as an antioxidant is yogurt. Yogurt is a food that contains a number of live bacteria that have a beneficial effect on health because it has antioxidant, antimicrobial, antidiarrheal activity and can boost the immune system. There are several factors that can affect the antioxidant activity of yogurt including temperature, storage conditions, and additional ingredients used such as adding fruit flavors. The purpose of this study was to determine the antioxidant activity of probiotics from yogurt drinks with various brands. Samples were taken from supermarkets in Medan City with 3 different brands coded A, B, and C. The antioxidant activity was determined by the DPPH (1,1-diphenyl-2-picrylhydrazyl) method using a visible spectrophotometer measured at wavelengths. 516 nm. The results showed that there were two samples of yogurt drink coded A and B which were included in the strong category and code C samples were included in the weak category. Yogurt drink with brand code A has the strongest antioxidant activity compared to other brand yogurt drinks (B and C) with IC50 values from samples code A (80.52 ml), B (90.14 ml), and C (194, 81 ml).